Lambda-cyhalothrin and its common metabolite differentially modulate thyroid disruption effects in Chinese lizards (Eremias argus). (15th October 2021) - Chang, Jing; Pan, Yifan; Liu, Wentao; Xu, Peng; Li, Wei; Wan, Bin
Abstract: Although the thyroid effects of pyrethroids on non-target organisms have been well studied, research on the toxic effects of pyrethorid metabolites is still limited. In this study, a type of representative Chinese lizards was used as the model and exposed to environmentally relevant concentrations of lambda-cyhalothrin (LCT) and 3-phenoxybenzoic acid (PBA) through cultivation on 3 and 15 μg/g soil to evaluate and compare their disruption effects on lizard hypothalamus-pituitary-thyroid (HPT) axis. The alterations occurred in lizards were examined through histopathology analyses, hormone level and gene expression measurements, the molecular binding interactions were analyzed in silico as well. The results showed that LCT exposure increased the plasma triiodothyronine (T3), thyroxine (T4) levels and the follicular epithelium heights of thyroid glands, whereas PBA induced no or much less degree of alterations. The ugt and dio2 gene expression in lizard liver was significantly up-regulated by LCT, but PBA caused less or opposite effects. The in silico homology simulation illustrated that LCT binds to TR α in the similar way of T3, while PBA binds to TR β in the same manner of T3. The results demonstrated that both LCT and its metabolite-PBA could disrupt lizard HPT axis but through distinct mechanisms. The information would facilitate the comprehensive environmental safety assessment of pyrethroids. Graphical abstract: Image 1 Highlights: LCT exposure increased the plasma T3 and T4 levels. The follicular epithelium heights of thyroid glands were increased by LCT treatment. LCT exposure mainly disrupted the dio2 and ugt gene levels. The trα and trβ genes were vital biomarkers after PBA exposure. The binding energy of PBA with TR α/ TR β was higher than that of LCT. Abstract : Both LCT and its metabolite-PBA could disrupt lizard thyroid system but through distinct mechanisms.